Fragile X messenger ribonucleoprotein 1 (FMRP) regulates glycolytic gene expression under chronic hypoxia in HCT116 cells - Yoko Ogura; Xiaoning Sun; Zaijun Zhang; Kentaro Kawata; Jinyu Wu; Ryuma Matsubara; Atsuko Nakanishi Ozeki; Kenzui Taniue; Rena Onoguchi-Mizutani; Shungo Adachi; Koh Nakayama; Nobuhito Goda; et al. (Scientific Reports)
Abstract Oxygen shortage, known as hypoxia, occurs commonly in both physiological and pathological conditions. Transcriptional regulation by hypoxia-inducible factors is a dominant regulatory mechanism controlling hypoxia-responsive genes during acute hypoxia; however, recent studies suggest that post-transcriptional regulation, including RNA degradation, also involves hypoxia-induced gene expression during the chronic hypoxia. In this study, we developed a method to quantify the contributions of RNA synthesis and degradation to differential gene expression, and identified 102 genes mainly regulated via RNA degradation under chronic hypoxia in HCT116 cells. Bioinformatics analysis showed that the genes mainly regulated by RNA degradation were involved in glycolysis. We examined changes in the RNA-binding ability of RNA-binding proteins by RNA interactome capture and statistical analysis using public databases. We identified fragile X messenger ribonucleoprotein 1 (FMRP) as an RNA-binding protein involved in the chronic hypoxia-induced increase in mRNAs encoding rate-limiting enzymes. This study emphasizes the importance of post-transcriptional gene regulation under chronic hypoxia in HCT116 cells.